Penerapan Direct-Fed Microbials untuk Optimalisasi Produktivitas Ternak Ruminansia pada Koperasi Produksi Ternak Maju Sejahtera - Silaban, Rikardo; Suryani, Heni; Putri, Dwi Desmiyeni (Seminar Nasional Lahan Suboptimal, 2024)
Silaban, R., Suryani, H., & Putri, D. D. (2024). Application of dierct-fed microbials to optimize ruminants productivity at Koperasi Ternak Maju Sejahtera. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembangg 21 Oktober 2024. (pp. 929–936). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The devotion aimed to optimize the use of feed in form of complete forage (CF) through Direct-Fed Microbials (DFM) supplementation, providing knowledge to the community, especially breeders  regarding good feed processing management, as well as providing the understanding to the community at Koperasi Produksi Ternak Maju Sejahtera to improve the potential quality of agricultural waste as feed in beef cattle fattening business. The activity method is carried out in a monologue, practice and evaluation by using descriptive questionnaires. The activity begins  with a presentation of material on ration formulation by utilizing the potential of local feed ingredients, the benefits of DFM, type of DFM microorganisms, the dosage of adding DFM and the way to combine DFM in feed. The community service results showed that breeders are very enthusiastic for the outreach of material provided. This also proven by the active role of participants, especially breeders, inthe question and answer session regarding how to use DFM in feed to improve livestock performance. In addition, regression analysis performed that two factors are respond agree with the average of 44 to 49.19% to respondentthe ability of farmers in using the product. Then, after the assistance of participant in processing the feed hi-technology by providing solid and liquid DFM, the regression analysis is also showed the radiness and desires of breeders with the highest score is about 38.33% to apply the DFM in order to increase their livestock performance. To sum up, after using the products, it has increased the average daily gain (ADG) and lowering the methane production in KPTMS.